PENGKAJIAN BEBERAPA ALGORITMA UNTUK MENGEVALUASI DAN MENGHITUNG LOSSES ENERGI PADA SISTEM DISTRIBUSI TENAGA LISTRIK - hilal, hamzah (Badan Pengkajian dan Penerapan Teknologi, 2012)
This paper presents an assessment of some algorithms to evaluate and costing energy losses in electrical power distribution systems. The algorithms had considered the accuracy and computational speed as variables. A simplified feeder serving large residensial and industrial loads is used to test the algoritms, and the results for each algorithm are compared.